STRATEGI GURU DALAM MEMBANGUN KEPERCAYAAN DIRI SISWA MELALUI DISKUSI KELOMPOK PADA MATA PELAJARAN SENI BUDAYA DI SEKOLAH UPT SMP NEGERI 35 MEDAN - Sani Susanti, Azzuhratul Khalisa Hrp, Veronika Br Sinuhaji, Seviyana Chaira Br Tarigan, Yesi Okta Hu (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
This study explores the role of group discussions in enhancing students' self-confidence. Based on theories of developmental psychology and education, a qualitative approach was used with observation and semi-structured interviews. The results indicate that group discussions enable students to interact, speak, and listen more confidently. By providing a supportive environment and appropriate strategies, group discussions can boost students' self-confidence. The implication is that teachers need to utilize various group discussion techniques to create supportive learning experiences and foster students' self-confidence.